Isolated Pulmonary Hydatid Cyst: A Rare Presentation in a Young Maasai Boy from Northern Tanzania. (1st October 2019) - Lodhia, Jay; Herman, Ayesiga; Philemon, Rune; Sadiq, Adnan; Mchaile, Deborah; Chilonga, Kondo
Abstract : Introduction . Hydatidosis is a parasitic manifestation caused by Echinococcus granulosus. It is characterized by cystic lesions in the liver and lungs. Diagnosis is based on typical history and radiological measures. Case presentation . A four-year-old boy presented with a one-year history of dry cough and difficulty in breathing which was of gradual progression. Computed tomography of the chest revealed a large11.7 cm × 8.6 cm × 11.0 cm cyst in the right hemithorax. The patient underwent thoracotomy and recovered well post procedure. Conclusion . This case report highlights that large hydatid cysts can be surgically removed with good outcome and the importance of realizing that the disease is a burden to the public health and is much neglected.